Responses of non‐native and native plant species to fluctuations of water availability in a greenhouse experiment - Wenchao Qin; Yan Sun; Heinz Müller‐Schärer; Wei Huang (Ecology and Evolution, 2024)
Abstract Water availability strongly influences the survival, growth, and reproduction of most terrestrial plant species. Experimental evidence has well documented the effect of changes in total amount of water availability on non‐native vs. native plants. However, little is known about how fluctuations in water availability affect these two groups, although more extreme fluctuations in water availability increasingly occur with prolonged drought and extreme precipitation events. Here, we grew seven non‐native and seven native plant species individually in the greenhouse. Then, we exposed them to four watering treatments, each treatment with the same total amount of water, but with different divisions: W1 (added water 16 times with 125 mL per time), W2 (8 times, 250 mL per time), W3 (4 times, 500 mL per time), and W4 (2 times, 1000 mL per time). We found that both non‐native and native plants produced the most biomass under medium frequency/magnitude watering treatments (W2 and W3). Interestingly, non‐native plants produced 34% more biomass with the infrequent, substantial watering treatment (W4) than with frequent, minor watering treatment (W1), whereas native plants showed opposite patterns, producing 26% more biomass with W1 than with W4. Differences in the ratio of root to shoot under few/large and many/small watering treatments of non‐native vs. native species probably contributed to their different responses in biomass production. Our results advance the current understanding of the effect of water availability on non‐native plants, which are affected not only by changes in amount of water availability but also by fluctuations in water availability. Furthermore, our results indicate that an increased few/large precipitation pattern expected under climate change conditions might further promote non‐native plant invasions. Future field experiments with multiple phylogenetically controlled pairs of non‐native and native species will be required to enhance our understanding of how water availability fluctuations impact on non‐native invasions.